Ancient horizontal transfers of retrotransposons between birds and ancestors of human pathogenic nematodes - Alexander Suh (Nature Portfolio, 2016)
Lymphatic filariasis and loiasis are diseases caused by insect-borne filarial nematodes. Here, Suh et al. identify a retrotransposon that is present in the genomes of these nematodes and seven tropical bird lineages, indicating two waves of horizontal gene transfer around 17–25 million years ago.